Peningkatan Infrasruktur Di Yayasan Nurul Hikmah Rebalas Melalui Bantuan Teknis Pemasangan Keramik Teras - Rif'atul Khusniah; Anisah Nur Fajarwati; Aulia Rahman; Ayisya Cindy Harifah; Indah Ria Riskiyah; Yehezkiel Septian Yoganata (Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity focused on improving the learning environment at Nurul Hikmah Foundation, located in Rebalas Village, Grati District, Pasuruan Regency. By providing technical assistance for ceramic tile installation on the foundation's terrace, we aimed to create a comfortable and attractive outdoor learning space for the children. The installation of ceramic tiles not only enhanced the aesthetics of space but also created a safe and stimulating environment for the young learners. This intervention is expected to positively impact on student engagement, academic performance, and overall school experience at Nurul Hikmah Foundation